Sewage sludge as a sealing layer for the remediation of sulphide-bearing mine tailings : ageing and degradation of the barrier material - Nason, Peter; Alakangas, Lena; Öhlander, Björn (Luleå tekniska universitet, Geovetenskap och miljöteknik, 2011)
Using sewage sludge as an organic barrier to mitigate oxygen diffusion to underlying sulphidic tailings was performed in experimental pilot-scale test cells, northern Sweden and was proved to be successful over an 8 year period (Nason et al., 2010). However, degradation and ageing of the sewage sludge may limit its function in the long-term as indicated by surface applications of sewage sludge, as the exposure of the material to atmospheric oxygen may cause aerobic degradation of the organic matter fraction (Peppas et al., 2000), nitrification (Cravotta, 1998) and subsequent structural disintegration (Ahlberg, 2006). A pilot-scale test cell with a 0.3m sewage sludge sealing layer capped by a 1.2m protective layer of glacial till was used to cover tailings. Quantification of the changing properties of the sewage sludge after an 8 year period occurred using temperature data and solid sludge and leachate geochemistry. It was found that all layers were frozen between December to April and that a perched water table formed above the sealing layer from April to August (Shcherbakova, 2006). The subsequent lack of contact of the sludge with oxygen minimised aerobic degradation of the organic fraction, prevented nitrification and created an anoxic environment in the sludge. Nitrate in the leachate was <1mg/l and the subsequent lack of acidification created a neutral pH in the sludge and underlying tailings. Elevated alkalinity (360-600 mg/l) and low sulphate (9-67 mg/l) in the leachate indicated that sulphate reduction by anaerobic degradation of the organic matter had occurred in the sludge. On average, the organic fraction was reduced by 80%, but was most prevalent at the sludge to tailings interface where 92% of the organic matter had been lost since deposition. Mass balance calculations of the sludge revealed a 19.6% total loss of volume due to the organic matter degradation and leaching of Cd, Cu, Hg, Zn and P that were elevated in the original sludge material. No structural degradation as experienced by surface ...